From Roman to early Christian Thessalonikē (Cambridge, Mass.)
xiv, 437, [5] sayfa
Keywords: “This volume brings together international scholars of religion, archaeologists, and scholars of art and architectural history to investigate social, political, and religious life in Roman and early Christian Thessalonikē, an important metropolis in the Hellenistic, Roman, and early Christian periods and beyond. This volume is the first broadly interdisciplinary investigation of Roman and early Christian Thessalonikē in English and offers new data and new interpretations by scholars of ancient religion and archaeology. The book covers materials usually treated by a broad range of disciplines: New Testament and early Christian literature, art historical materials, urban planning in antiquity, material culture and daily life, and archaeological artifacts from the Roman to the late antique period“ --